Proceedings of the 1st Standardized Knowledge Representation and Ontologies for Robotics and Automation Workshop - Gonçalves, P.J.S. (2015)
Welcome to IEEE-ORA (Ontologies for Robotics and Automation) IROS workshop. This is the 1st edition of the workshop on! Standardized Knowledge Representation and Ontologies for Robotics and Automation. The IEEE-ORA 2014 workshop was held on the 18th September, 2014 in Chicago, Illinois, USA. In!the IEEE-ORA IROS workshop, 10 contributions were presented from 7 countries in North and South America, Asia and Europe. The presentations took place in the afternoon, from 1:30 PM to 5:00 PM. The first session was dedicated to “Standards for Knowledge Representation in Robotics”, where presentations were made from the IEEE working group standards for robotics and automation, and also from the ISO TC 184/SC2/WH7. The second session was dedicated to “Core and Application Ontologies”, where presentations were made for core robotics ontologies, and also for industrial and robot assisted surgery ontologies. Three posters were presented in emergent applications of ontologies in robotics. We would like to express our thanks to all participants. First of all to the authors, whose quality work is the essence of this workshop. Next, to all the members of the international program committee, who helped us with their expertise and valuable time. We would also like to deeply thank the IEEE-IROS 2014 organizers for hosting this workshop. Our deep gratitude goes to the IEEE Robotics and Automation Society, that sponsors! the IEEE-ORA group activities, and also to the scientific organizations that kindly agreed to sponsor all the workshop authors work.